The role of unbalanced segmental duplication in sex chromosome evolution in Australian ridge-tailed goannas - Jason Dobry; Zexian Zhu; Qi Zhou; Erik Wapstra; Janine E. Deakin; Tariq Ezaz (Scientific Reports)
Abstract Varanids are known for conserved sex chromosomes, but there are differences in the size of the W chromosome but not in morphology among species representing varying stages of sex chromosome evolution. We tested for homology of the ZW sex chromosome system with size differences in varanids among four species from two lineages in Australia, the Odatria and the Gouldii. We found that while DNA sequences of the sex chromosomes are conserved in the species we tested, we also identified a homologous region on an enlarged autosomal microchromosome that shares sequences with the W chromosome in some isolated populations of V. acanthurus and V. citrinus from the Odatria lineage. The enlarged microchromosome was unpaired in all individuals tested and is likely an unbalanced segmental duplication translocated between chromosome 1, the W, and another microchromosome. This suggests an ancient balanced duplication homologous to the W and the terminal region of the long arm of chromosome 1. The most parsimonious explanation is that the duplicated region likely originated on chromosome 1. We hypothesised in our reconstruction that genes and related DNA sequences associated with the sex-linkage group have likely originated on an autosome. Subsequently, the sequences may have undergone duplication and translocation to the W chromosome, followed by the accumulation of lineage specific repeat elements and amplifications on the W at different rates in various lineages. Lastly, these sequences are likely to have undergone duplication and translocation to another autosomal microchromosome. Given the role of segmental duplications and translocations as important evolutionary drivers of speciation in other taxa, together with the rapid speciation that has occurred in Australian varanids, our findings provide broader insight into the evolutionary pathway leading to rapid chromosomal and genic divergence of species.